Strong tidal variations in ice flow observed across the entire Ronne Ice Shelf and adjoining ice streams - Rosier, Sebastian H. R.; Gudmundsson, G. Hilmar; King, Matt A.; Nicholls, Keith W.; Makinson, Keith; Corr, Hugh F. J. (Earth System Science Data, 2018)
We present a compilation of GPS time series, including those for previously unpublished sites, showing that flow across the entire Ronne Ice Shelf and its adjoining ice streams is strongly affected by ocean tides. Previous observations have shown strong horizontal diurnal and semidiurnal motion of the ice shelf, and surface flow speeds of Rutford Ice Stream (RIS) are known to vary with a fortnightly ( M sf ) periodicity. Our new data set shows that the M sf flow modulation, first observed on RIS, is also found on Evans, Talutis, Institute, and Foundation ice streams, i.e. on all ice streams for which data are available. The amplitude of the M sf signal increases downstream of grounding lines, reaching up to 20 % of mean flow speeds where ice streams feed into the main ice shelf. Upstream of ice stream grounding lines, decay length scales are relatively uniform for all ice streams but the speed at which the M sf signal propagates upstream shows more variation. Observations and modelling of tidal variations in ice flow can help constrain crucial parameters that determine the rate and extent of potential ice mass loss from Antarctica. Given that the M sf modulation in ice flow is readily observed across the entire region at distances of up to 80 km upstream of grounding lines, but is not completely reproduced in any existing numerical model, this new data set suggests a pressing need to identify the missing processes responsible for its generation and propagation. The new GPS data set is publicly available through the UK Polar Data Centre at http://doi.org/10.5285/4fe11286-0e53-4a03-854c-a79a44d1e356 .